A comprehensive review of drop weight impact testing: Evaluating the Pros and Cons in fiber-reinforced concrete performance assessment - Murali G.; Wong L.S.; Abid S.R. (Elsevier Ltd, 2025)
This article provides a comprehensive review of current literature, concentrating on the impact resistance of various fibrous concretes subjected to drop-weight impact loads, as assessed by the ACI Committee 544. Previous studies have identified substantial dispersion and unacceptable variances in test results, leading researchers to implement statistical methods to mitigate these issues. The novelty of this review lies in its rigorous examination of the effects of various types of fibrous concrete on the impact strength of cylindrical and prism specimens. Notably, the ACI Committee 544 drop weight test results, which are limited to the scope of this review, have not been previously examined by any researcher. Moreover, this review offers a detailed analysis of the variations in impact test results and evaluates the statistical methods employed by researchers. Additionally, it discusses the ACI Committee 544 testing methodologies and the modifications introduced by researchers, assessing the advantages and disadvantages of these testing methods as an objective and offering new recommendations. Based on the data from the literature, the drop weight test results are scattered and unreliable, and a statistical tool is required to clarify the results. Line and cross-notched specimens and load transfer plates introduce a more regulated and systematic predefined cracking pattern. Nevertheless, the practical implementation of the modified test setup proves challenging, with results still exhibiting scattering within this configuration. This review underscores the pressing need for further research to fully understand the necessary modifications in impact testing methodologies for concrete-containing fibers. ? 2024 Elsevier Ltd